MEDIA SOSIAL SEBAGAI MEDIA PERGESERAN INTERAKSI SOSIAL REMAJA - Intan Putri; Dendi; Nanda Syukerti; Ahmad Iman Mulyadi; Insan Maulana (Universitas Sumatera Selatan, 2022)
The existence of new media or new media cannot be separated from the rapid development of technology and communication. The internet as a product of communication technology, although it has been developing for quite a long time, is still a topic of discussion for the public or the community until now. Audiences are not only talking about the “power” or positive impact of the Internet, but also the negative impact that comes with it.In carrying out the current communication process, it can be done in various ways, it can be in the form of face-to-face communication, through writing in letters, by telephone and the most often used now is through computers. In communication through computers or Computer Mediated Communication, communication activities are carried out in various ways such as email, instant messaging, social media, the most important of which can be connected to each other through the internet network.Social interaction is a condition for the occurrence of social activities. In doing interaction there are conditions that must be met, namely social contact and social communication. Information technology in the era of globalization is growing rapidly in people's lives. The use of increasingly sophisticated communication facilities provides opportunities for each individual to access information as desired and can communicate easily without thinking about time.Based on this, this paper explains how the 'momentum' of Eid Al-Fitr 1438H is a place for interaction with or friendship between teenagers. In order to wish you a happy Eid Al-Fitr 1438H, not a few people use social media facilities. so the researcher can conclude that the largest social media users in Adolescent Social Interaction in order to wish a happy Eid Al-Fitr 1438H are on social media facebook by 45%. Followed by Instagram users (26%), Whatsapp (20%) and BBM (9%). This can be seen how the teenager interacts socially with those who use social media Facebook, BBM, Instagram, and Whatsapp. Whether interacting personally, in groups, replying to comments, or posting photos and videos on social media.